Development Of Educational Posters Based On The Concept Of Gamification As An Interactive Learning Media On Science Material For Class Vi Primary School - Sudiartini, Ni Nyoman; Putrayasa, Ida Bagus; Sudiana, I Nyoman (UNIVERSITAS PAKUAN, 2024)
This research aims to (1) produce educational posters based on the concept of gamification as an interactive learning medium for science material that are valid and practical, and (2) test the effectiveness of educational posters based on the concept of gamification as an interactive learning medium for science material. The research subjects were media and materials experts, 56 class VI students at SD Negeri 4 Ungasan and 2 teachers. Collection methods include questionnaires and tests, research instruments in the form of validity questionnaire sheets, practicality questionnaire sheets, and science learning outcomes tests. Data analysis uses percentage calculations and one sample t test. The research results show that (1) The validity of educational posters based on the concept of gamification as an interactive learning medium regarding science material through material experts is 90.7% very valid and the validity of media experts is 95% very valid. (2) Educational Posters Based on Gamification Concepts as Interactive Learning Media on Science Material by 97.3% of teachers and 100% of students are very practical and suitable for use (3) Educational Posters Based on Gamification Concepts as Interactive Learning Media in Science Learning are effective in increasing the average Science learning outcomes at SD Negeri 4 Ungasan.